2021
DOI: 10.3389/pore.2021.1610039
|View full text |Cite
|
Sign up to set email alerts
|

Syntaxin-1 and Insulinoma-Associated Protein 1 Expression in Breast Neoplasms with Neuroendocrine Features

Abstract: Introduction: A subset of breast neoplasia is characterized by features of neuroendocrine differentiation. Positivity for Neuroendocrine markers by immunohistochemistry is required for the diagnosis. Sensitivity and specificity of currently used markers are limited; based on the definitions of WHO Classification of Tumours, 5th edition, about 50% of breast tumors with features of neuroendocrine differentiation express chromogranin-A and 16% express synaptophysin. We assessed the applicability of two novel mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Others adopted a 1% cut-point. 6 Additional studies are required to explore which cut-point is clinically and biologically meaningful, especially since Razvi et al suggested that INSM1 expression in breast tumors is associated with a more favorable outcome. 7 We agree with Kawasaki et al that any breast lesion harboring the aforementioned "classic" morphological features suggestive of neuroendocrine differentiation should provoke a more detailed work-up by means of immunohistochemistry for synaptophysin, chromogranin A and INSM1, as these stains might aid to establish a final diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Others adopted a 1% cut-point. 6 Additional studies are required to explore which cut-point is clinically and biologically meaningful, especially since Razvi et al suggested that INSM1 expression in breast tumors is associated with a more favorable outcome. 7 We agree with Kawasaki et al that any breast lesion harboring the aforementioned "classic" morphological features suggestive of neuroendocrine differentiation should provoke a more detailed work-up by means of immunohistochemistry for synaptophysin, chromogranin A and INSM1, as these stains might aid to establish a final diagnosis.…”
mentioning
confidence: 99%
“…Others adopted a 1% cut-point. 6 Additional studies are required to explore which cut-point is clinically and biologically meaningful, especially since Razvi et al suggested that INSM1 expression in breast tumors is associated with a more favorable outcome. 7…”
mentioning
confidence: 99%